2017
DOI: 10.1080/10408398.2017.1360837
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin intake and potential chronobiological effects on human health

Abstract: Melatonin is an indolamine with a recognized chronobiotic role. In turn, the supplementation of melatonin through capsules has been shown to be efficient in the modulation of inflammatory markers, oxidative stress, as well as in the control of hypertension and metabolic syndrome. However, the science of nutrition is interested in the study of the food sources of this hormone and its possible therapeutic effects. Thus, this review aimed to identify and present scientific papers that quantified melatonin in food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In one of these studies, a positive correlation was found between melatonin-rich foods and clinical-metabolic indicators. Also, melatonin concentration varies markedly among various foods, and its concentration may change during the food products’ preparation [133].…”
Section: Melatonin Supplementation and Its Health Effects For Humansmentioning
confidence: 99%
“…In one of these studies, a positive correlation was found between melatonin-rich foods and clinical-metabolic indicators. Also, melatonin concentration varies markedly among various foods, and its concentration may change during the food products’ preparation [133].…”
Section: Melatonin Supplementation and Its Health Effects For Humansmentioning
confidence: 99%
“…So, the presence of phytomelatonin in beverages derived from plant products are not surprising. In fact, phytomelatonin has been quantified in large amount in the most popular beverages such as coffee, tea, juice, herbal infusions, wine and beer [ 11 , 96 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 ]. In alcoholic drinks like beer [ 122 , 130 ] and wine [ 127 , 131 ], the melatonin amount was of 0.09 ± 0.01 ng/mL in beer [ 130 ] and up to 129.5 ± 3.5 ng/mL in wine [ 122 , 130 ].…”
Section: Melatonin and Potential Nutritional Impact In Health And mentioning
confidence: 99%
“…As a neurohormone, melatonin is characterized with pleiotropic activities, such as treating insomnia ( 19 ), inhibiting tumor growth ( 20 , 21 ), and being utilized as an adjuvant of cancer therapies ( 22 , 23 ). Numerous investigations have indicated that melatonin also has many benefits on the cardiovascular system, including regulation of atherosclerosis, depression of hypertension, and prevention of hypertensive heart disease ( 24 26 ). Moreover, melatonin alleviated hemodynamics and pulmonary vascular remodeling in hypoxic PH rats ( 18 ), decreased pulmonary vascular remodeling and oxygen sensitivity in pulmonary hypertensive newborn lambs ( 16 ), and alleviated vascular disorders in monocrotaline-induced PH rats ( 27 ).…”
Section: Introductionmentioning
confidence: 99%